MODEL BLENDED LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP WAHID HASYIM MALANG - Devi Widya Arisanti; Muhammad Sulistiono; Bagus Cahyanto (VICRATINA, 2022)
At the beginning of the pandemic, learning in the world of education in Indonesia turned becomes online learning with several problems felt by students and teachers, so that learning was re-implementation with face-to-face learning, so for the first time Wahid Hasyim Junior High School Malang used the blended learning model in learning. Based on that, our study explore deeply about “The Blended Learning Model in Islamic Education Learning at Wahid Hasyim Junior High School Malang”. This study includes the planning, implementation, and disadvantages and advantages of the blended learning model in Islamic Education at Wahid Hasyim Junior High School Malang. This Study used qualitative research method with case study type approach. This study shows that the planning of blended learning model is to form a blended learning teams, involving training related to the use of applications, prepare learning tools (RPP), learning materials and media, online assignments, and selections of learning application. The implementation model of blended learning in Islamic Education consisted of preliminary activities, core activities, and closing activities. Based on the result of the study, it was found that there were disadvantages dan advantages of the blended learning model in learning Islamic Education at Wahid Hasyim Junior High School Malang